Weak $α$-skew Armendariz ideal - Nikmehr, M. J.; Pazoki, M.; Tavallaee, H. A. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We introduce the concept of weak $α$-skew Armendariz ideals and investigate their properties. Moreover, we prove that $I$ is a weak $α$-skew Armendariz ideal if and only if $I[x]$ is a weak $α$-skew Armendariz ideal. As a consequence, we show that $R$ is a weak $α$-skew Armendariz ring if and only if $R[x]$ is a weak $α$-skew Armendariz ring.